Should I post? The relationships among social media use, emotion recognition, and mental health - Scarpulla, Emily; Stosic, Morgan D.; Weaver, Adele E.; Ruben, Mollie A. (Frontiers in Psychology, 2023)
Introduction While increased time spent on social media can be negatively related to one’s overall mental health, social media research often fails to account for what behaviors users are actually engaging in while they are online. The present research helps to address this gap by measuring participants’ active and passive social media behavioral styles and investigates whether and how these two social media behavioral styles are related to depression, anxiety, and stress, and the mediating role of emotion recognition ability in this relationship. Methods A pre-study (N = 128) tested whether various social media behaviors reliably grouped into active and passive behavioral styles, and a main study (N = 139) tested the relationships between social media use style, emotion recognition, and mental health. Results While we did not find evidence of a mediating relationship between these variables, results supported that more active social media use was related to more severe anxiety and stress as well as poorer emotion recognition skill, while passive social media use was unrelated to these outcomes. Discussion These findings highlight that, beyond objective time spent on social media, future research must consider how users are spending their time online.